Amorphous carbon-based coating resistant to atomic oxygen erosion as well as preparation method and application of amorphous carbon-based coating

By stacking amorphous carbon-based coatings with chromium, chromium nitride, chromium nitrogen carbide layers and lead-doped hydrogenated amorphous carbon layer on the surface of the spacecraft substrate, the atomic oxygen erosion problem faced by the spacecraft in a low-Earth orbit environment is solved, low friction and high corrosion resistance are achieved, and service life is extended and operation stability is improved.

CN119736594APending Publication Date: 2025-04-01ARMOR ACADEMY OF CHINESE PEOPLES LIBERATION ARMY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411926857.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Spacecraft faces extreme atomic oxygen erosion in low-Earth orbit environments, resulting in lubrication failures and affecting operational reliability and safety. The existing lubricants are difficult to meet the requirements of the space environment.

Method used

An amorphous carbon-based coating is used for stacking transition layers and functional layers in sequence on the substrate surface. The transition layer includes a chromium layer, a chromium nitride layer and a chromium nitrogen carbonide layer. The functional layer is a lead-doped hydrogenated amorphous carbon layer. The residual stress is reduced and the adhesion strength is improved through gradient structure design.

Benefits of technology

Maintain ultra-low friction in a vacuum environment and the friction coefficient remains low after atomic oxygen erosion, extending service life and improving operating stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736594A_ABST
    Figure CN119736594A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of coating preparation, and particularly relates to an atomic oxygen erosion resistant amorphous carbon-based coating as well as a preparation method and application thereof. The invention provides an amorphous carbon-based coating resistant to atomic oxygen corrosion. The amorphous carbon-based coating comprises a transition layer and a functional layer which are sequentially arranged on the surface of a base body in a stacked mode. The transition layer comprises a chromium layer, a chromium nitride layer and a nitrogen chromium carbide layer which are arranged in a stacked mode. The chromium layer is in contact with the base body; the functional layer is a lead-doped hydrogenated amorphous carbon layer, and the nitrogen chromium carbide layer is in contact with the functional layer. According to the invention, the transition layer adopts a gradient structure design, so that the residual stress of the coating can be effectively reduced, and the adhesion strength of the coating and the substrate can be improved. According to the invention, the functional layer is based on the amorphous carbon coating, the hydrogen element is added to reduce the friction coefficient, the Pb element is added to enhance the atomic oxygen corrosion resistance of the coating, the coating is suitable for being applied to various moving parts in a space environment, the service life can be effectively prolonged, and the operation stability can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating preparation, and in particular relates to an amorphous carbon-based coating resistant to atomic oxygen corrosion and a preparation method and application thereof. Background Art

[0002] Low Earth Orbit (LEO) is 160 to 2000 km from the Earth and is the most accessible area for satellites and spacecraft. Nearly 85% of active satellites are currently operating in this area. In this area, spacecraft face extreme operating environments and harsh space radiation environments, especially atomic oxygen erosion.

[0003] The beam flux of atomic oxygen (AO) at LEO is 4×10 12 ~10 15 atoms / cm 2 ·s, and the impact energy of each atom is greater than 5eV. Lubrication failure of spacecraft seriously affects the reliability and safety of operation, and may even cause serious damage to the space system. So far, almost no lubricant has been proven to accurately meet the requirements of the operating parameters of spacecraft mechanical components in the space environment.

[0004] Therefore, there is an urgent need for a lubricating coating that is resistant to atomic oxygen corrosion and can be used in a space environment. Summary of the invention

[0005] The purpose of the present invention is to provide an amorphous carbon-based coating resistant to atomic oxygen erosion, and a preparation method and application thereof. The amorphous carbon-based coating provided by the present invention can not only maintain ultra-low friction in a vacuum environment, but also maintain a low friction coefficient after AO erosion.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides an amorphous carbon-based coating resistant to atomic oxygen corrosion, comprising a transition layer and a functional layer sequentially stacked on the surface of a substrate;

[0008] The transition layer comprises a chromium layer, a chromium nitride layer and a chromium nitride carbide layer which are stacked; the chromium layer is in contact with the substrate;

[0009] The functional layer is a lead-doped hydrogenated amorphous carbon layer, and the chromium carbide nitride layer is in contact with the functional layer.

[0010] Preferably, the thickness of the chromium layer is 50-100 nm; the thickness of the chromium nitride layer is 100-150 nm; the thickness of the chromium nitride carbide layer is 150-250 nm;

[0011] The thickness of the transition layer is 0.3-0.5 μm.

[0012] Preferably, the atomic percentage of lead in the functional layer is 30-50%, and the atomic percentage of carbon is 50-70%;

[0013] The thickness of the functional layer is 2.5-3.5 μm.

[0014] Preferably, the substrate comprises a single crystal silicon wafer or a stainless steel substrate;

[0015] The surface roughness of the substrate does not exceed 1 / 10 of the thickness of the amorphous carbon-based coating.

[0016] Preferably, the surface roughness of the amorphous carbon-based coating is 1 to 10 nm; and the vacuum average friction coefficient of the amorphous carbon-based coating is 0.005 to 0.02.

[0017] The present invention also provides a method for preparing the amorphous carbon-based coating resistant to atomic oxygen corrosion as described in the above technical solution, comprising the following steps:

[0018] pretreating the substrate to obtain a pretreated substrate;

[0019] A transition layer and a functional layer are sequentially prepared on the surface of the pretreated substrate to obtain the amorphous carbon-based coating.

[0020] Preferably, the pretreatment process is: using argon plasma to bombard the substrate for etching pretreatment;

[0021] The bombardment etching pretreatment condition parameters include: using inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -500 to -700 V, and a time of 20 to 30 minutes.

[0022] Preferably, the transition layer and the functional layer are both prepared by magnetron sputtering deposition;

[0023] The magnetron sputtering deposition conditions of the chromium layer include: using an inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power source power corresponding to the chromium target of 1.5 to 2 kW, and a sputtering time of 20 to 30 min;

[0024] The magnetron sputtering deposition conditions of the chromium nitride layer include: using an inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power supply power corresponding to the chromium target of 1.5 to 2 kW, a nitrogen flow rate of 30 to 50 sccm, and a sputtering time of 20 to 30 min;

[0025] The condition parameters of the magnetron sputtering deposition of the chromium nitride carbide layer include: using an inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power supply power corresponding to a chromium target of 1.5 to 2 kW, a sputtering power supply power corresponding to a graphite target of 4.5 to 6 kW, a nitrogen flow rate of 30 to 50 sccm, and a sputtering time of 20 to 30 min.

[0026] Preferably, the condition parameters for magnetron sputtering deposition of the functional layer include: using inert gas as the gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power supply power corresponding to the graphite target of 4.5 to 6 kW, a sputtering power supply power corresponding to the lead target of 1 to 2 kW, a hydrocarbon-containing gas flow rate of 80 to 100 sccm, and a sputtering time of 150 to 180 min.

[0027] The present invention also provides the use of the atomic oxygen corrosion-resistant amorphous carbon-based coating described in the above technical solution or the atomic oxygen corrosion-resistant amorphous carbon-based coating prepared by the preparation method described in the above technical solution on devices used in space environments.

[0028] The present invention provides an amorphous carbon-based coating resistant to atomic oxygen corrosion, comprising a transition layer and a functional layer stacked in sequence on the surface of a substrate; the transition layer comprises a chromium layer, a chromium nitride layer and a chromium nitride carbide layer stacked in sequence; the chromium layer is in contact with the substrate; the functional layer is a lead-doped hydrogenated amorphous carbon layer, and the chromium nitride carbide layer is in contact with the functional layer.

[0029] In the present invention, the transition layer adopts a gradient structure design, which can effectively reduce the residual stress of the coating and improve the adhesion strength between the coating and the substrate. In the present invention, the functional layer is based on an amorphous carbon coating (aC coating), and hydrogen is added to reduce the friction coefficient. The specific mechanism is as follows: in a vacuum environment, the carbon atoms on the surface of the non-hydrogenated amorphous carbon coating have free dangling bonds. When friction occurs, the carbon dangling bonds will have a strong adhesion effect with the friction material, thereby increasing the friction coefficient and aggravating the wear; when hydrogen is added to the amorphous carbon coating, the dangling bonds on the surface of the amorphous carbon coating are saturated with hydrogen, and a layer of ultra-thin polymer-like hydrocarbons is formed on the surface of the coating, which is easily sheared during the friction process, so the friction coefficient is very low; at the same time, Pb element is added to enhance the atomic oxygen erosion resistance of the coating. The specific mechanism is as follows: soft metal lead itself is a soft metal lubricating material, which has the advantage of a low friction coefficient in any environment. In an atomic oxygen environment, the hydrogenated amorphous carbon coating is easily irradiated by atomic oxygen and dehydrogenated. When lead element is present, lead will preferentially react with oxygen to form lead oxide, thereby protecting the carbon coating from erosion. At the same time, lead oxide also has a certain lubricating effect. Therefore, the amorphous carbon-based coating provided by the present invention is suitable for application on the surfaces of various moving parts in a space environment, and can effectively extend the service life and improve the operational stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is an AFM surface morphology image of the amorphous carbon-based coating obtained in Example 1;

[0031] Figure 2 The surface microstructure of the amorphous carbon-based coating obtained in Example 1;

[0032] Figure 3 This is a Raman spectrum of the amorphous carbon-based coating obtained in Example 1;

[0033] Figure 4 This is a test diagram of the adhesion strength of the amorphous carbon-based coating obtained in Example 2;

[0034] Figure 5 The vacuum friction coefficient test result of the amorphous carbon-based coating obtained in Example 2;

[0035] Figure 6 This is a surface microscopic morphology of the amorphous carbon-based coating obtained in Example 2 after AO irradiation;

[0036] Figure 7 The vacuum friction coefficient test result of the amorphous carbon-based coating obtained in Example 2 after AO irradiation;

[0037] Figure 8 This is the vacuum friction coefficient test result of the amorphous carbon-based coating obtained in Example 3. DETAILED DESCRIPTION

[0038] The present invention provides an amorphous carbon-based coating resistant to atomic oxygen corrosion, comprising a transition layer and a functional layer sequentially stacked on the surface of a substrate;

[0039] The transition layer comprises a chromium layer, a chromium nitride layer and a chromium nitride carbide layer which are stacked; the chromium layer is in contact with the substrate;

[0040] The functional layer is a lead-doped hydrogenated amorphous carbon layer (aC:H:Pb coating), and the chromium carbide nitride layer is in contact with the functional layer.

[0041] In the present invention, the thickness of the chromium layer is preferably 50-100nm, specifically 50nm, 60nm, 70nm, 80nm, 90nm, 100nm; the thickness of the chromium nitride layer is preferably 100-150nm, specifically 50nm, 60nm, 70nm, 80nm, 90nm, 100nm; the thickness of the chromium carbide nitride layer is preferably 150-250nm, specifically 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm; the thickness of the transition layer is preferably 0.3-0.5μm, specifically 0.3μm, 0.4μm, 0.5μm.

[0042] In the present invention, the atomic percentage of lead in the functional layer is 30-50%, specifically 30%, 35%, 40%, 45%, and 50%; the atomic percentage of carbon is 50-70%, specifically 50%, 55%, 60%, 65%, and 70%; the thickness of the functional layer is preferably 2.5-3.5μm, specifically 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3.0μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, and 3.5μm.

[0043] In the present invention, the substrate preferably includes a single crystal silicon wafer or a stainless steel substrate; the surface roughness of the substrate is preferably no more than 1 / 10 of the thickness of the amorphous carbon-based coating, and the roughness is further preferably less than 0.3 μm. In the present invention, the stainless steel substrate preferably includes gear steel or bearing steel, with a hardness of no less than 20 HRC, and the bearing steel is preferably GCr15 bearing steel.

[0044] In the present invention, the surface roughness of the amorphous carbon-based coating is preferably 1 to 10 nm; the vacuum friction coefficient of the amorphous carbon-based coating is preferably 0.005 to 0.02.

[0045] The present invention also provides a method for preparing the amorphous carbon-based coating resistant to atomic oxygen corrosion as described in the above technical solution, comprising the following steps:

[0046] pretreating the substrate to obtain a pretreated substrate;

[0047] A transition layer and a functional layer are sequentially prepared on the surface of the pretreated substrate to obtain the amorphous carbon-based coating.

[0048] The present invention pre-treats the substrate to obtain a pre-treated substrate.

[0049] Before the pretreatment, the present invention also preferably includes cleaning the substrate, and the cleaning is preferably ultrasonic cleaning in anhydrous ethanol, acetone and deionized water for 30 minutes in sequence. In the present invention, impurities, adsorbents and oil stains on the surface of the substrate can be effectively removed by cleaning.

[0050] In the present invention, when the substrate is a stainless steel substrate, before the cleaning, it is preferred that the stainless steel substrate is subjected to grinding, sandpaper polishing, and fluid polishing in sequence.

[0051] In the present invention, the pretreatment process is preferably: using argon plasma to bombard the substrate for etching pretreatment; the bombardment etching pretreatment condition parameters preferably include: using inert gas as the gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -500 to -700 V, and a time of 20 to 30 minutes.

[0052] After obtaining the pretreated substrate, the present invention sequentially prepares a transition layer and a functional layer on the surface of the pretreated substrate to obtain the amorphous carbon-based coating.

[0053] In the present invention, the equipment used for the pretreatment, preparation of the transition layer and the functional layer is preferably a large closed-loop unbalanced magnetron sputtering device. In the present invention, before the substrate is pretreated, it is also preferred to clean the vacuum chamber and target material used for magnetron sputtering deposition to prevent impurities from contaminating the amorphous carbon-based coating. In the present invention, the cleaning condition parameters preferably include: using an inert gas as a gas source, a flow rate of 100 to 150 sccm, a bias voltage of 120 to 150 V, and a cleaning time of 20 to 30 minutes.

[0054] In the present invention, the conditions and parameters for magnetron sputtering deposition of the chromium layer preferably include: using inert gas as the gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power supply power corresponding to the chromium target of 1.5 to 2 kW, and a sputtering time of 20 to 30 min.

[0055] In the present invention, the condition parameters for magnetron sputtering deposition of the chromium nitride layer preferably include: using an inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power supply power corresponding to the chromium target of 1.5 to 2 kW, a nitrogen flow rate of 30 to 50 sccm, and a sputtering time of 20 to 30 min.

[0056] In the present invention, the condition parameters of the magnetron sputtering deposition of the chromium carbide nitride layer preferably include: using an inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power supply power corresponding to the chromium target of 1.5 to 2 kW, a sputtering power supply power corresponding to the graphite target of 4.5 to 6 kW, a nitrogen flow rate of 30 to 50 sccm, and a sputtering time of 20 to 30 min.

[0057] In the present invention, the transition layer adopts a gradient structure design, which can effectively reduce the residual stress of the coating and improve the adhesion strength between the coating and the substrate.

[0058] In the present invention, the condition parameters of the magnetron sputtering deposition of the functional layer preferably include: using an inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power supply power corresponding to a graphite target of 4.5 to 6 kW, a sputtering power supply power corresponding to a lead target of 1 to 2 kW, a hydrocarbon-containing gas flow rate of 80 to 100 sccm, and a sputtering time of 150 to 180 min. The hydrocarbon-containing gas preferably includes one or more of acetylene, methane and isobutane.

[0059] In the present invention, the inert gas used in the preparation process preferably includes argon or helium, the purity of the inert gas is preferably 99.999%, the purity of nitrogen is preferably 99.99%, the purity of the hydrocarbon-containing gas is preferably 99.99%, and the purity of the chromium target, graphite target and lead target used are preferably greater than or equal to 99.95%.

[0060] In the present invention, the functional layer is based on an amorphous carbon coating (aC coating), hydrogen elements are added to reduce the friction coefficient, and Pb elements are added to enhance the coating's resistance to atomic oxygen corrosion. It is suitable for use in various moving parts in a space environment, and can effectively extend service life and improve operational stability.

[0061] The present invention also provides the use of the atomic oxygen corrosion-resistant amorphous carbon-based coating described in the above technical solution or the atomic oxygen corrosion-resistant amorphous carbon-based coating prepared by the preparation method described in the above technical solution on devices used in space environments.

[0062] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0063] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0064] In the following embodiments, the purity of argon is 99.999%, the purity of nitrogen is preferably 99.99%, the purity of acetylene is 99.99%, and the purity of the chromium target, graphite target and lead target used are all greater than 99.95%.

[0065] Example 1

[0066] (1) The substrate is a single-sided polished single-crystal silicon wafer with a surface roughness of 0.025 μm, which is ultrasonically cleaned in anhydrous ethanol, acetone, and deionized water in an ultrasonic cleaning machine for 30 min;

[0067] The selected equipment is a large closed-loop unbalanced magnetron sputtering equipment; the cleaning of the inside of the vacuum chamber and the sputtering target: high-purity argon gas is used as the gas source, the flow rate is 100sccm, the bias voltage is 150V, and the cleaning time is 30min;

[0068] (2) The substrate was pretreated by bombardment etching: argon gas was used as the gas source, the flow rate was 100 sccm, the negative bias voltage was -700 V, and the cleaning time was 30 min;

[0069] (3) preparing a transition layer, wherein the transition layer has a gradient structure: Cr / CrN / CrCN;

[0070] Magnetron sputtering deposition of Cr layer: Ar flow rate is 100 sccm, negative bias voltage is -100 V, sputtering power corresponding to chromium target is 2 kW, sputtering time is maintained for 30 min, and a Cr layer with a thickness of 100 nm is obtained;

[0071] Magnetron sputtering deposition of CrN layer: Ar flow rate is 100 sccm, negative bias voltage is -100 V, sputtering power source power corresponding to chromium target is 2 kW, nitrogen flow rate is controlled to be 50 sccm, sputtering time is maintained for 30 min, and a CrN layer with a thickness of 150 nm is obtained;

[0072] Magnetron sputtering deposition of CrCN layer: the argon flow rate is 100 sccm, the negative bias voltage is -100 V, the sputtering power corresponding to the chromium target is 2 kW, the sputtering power corresponding to the graphite target is 6 kW, the nitrogen flow rate is controlled to be 50 sccm, the sputtering time is maintained at 30 min, and a CrCN layer with a thickness of 250 nm is obtained.

[0073] (4) Preparation of functional layer (aC:H:Pb coating)

[0074] Magnetron sputtering deposition of the functional layer: control the argon flow rate to 100 sccm, the negative bias voltage to -100 V, the sputtering power corresponding to the graphite target is 6 kW, the sputtering power corresponding to the lead target is 2 kW, control the acetylene flow rate to 100 sccm, maintain the sputtering time to 180 min, and obtain a functional layer with a thickness of 3.0 μm.

[0075] Example 2

[0076] An amorphous carbon-based coating was prepared in the manner of Example 1, except that the substrate was GCr15 bearing steel, and the surface roughness of the GCr15 bearing steel was about 0.1 μm after grinding, sandpaper polishing and fluid polishing.

[0077] Example 3

[0078] The amorphous carbon-based coating was prepared in the manner of Example 2, except that the argon gas flow rate was adjusted to 150 sccm during the preparation of the transition layer.

[0079] Performance Testing

[0080] Figure 1 This is an AFM surface morphology image of the amorphous carbon-based coating obtained in Example 1. It can be seen that the surface of the coating is relatively smooth, and the test surface roughness result is 7.47 nm.

[0081] Figure 2 The surface micromorphology of the amorphous carbon-based coating obtained in Example 1 shows that the surface morphology of the coating is cauliflower-shaped and the surface is composed of particles with a size of hundreds of nanometers. The surface particles gather together to form larger clusters and obvious cracks are visible between the clusters.

[0082] Figure 3 The Raman spectrum of the amorphous carbon-based coating obtained in Example 1 shows that the coating sample has a Raman spectrum of 800-2000 cm -1 The asymmetric broad peak in the range of 1580 cm-1 was observed, indicating that the carbon in the coating was amorphous. The Raman spectrum of the Pb / H-DLC coating was deconvoluted into a peak at 1580 cm-1 by Gaussian fitting. -1 The G peak centered at 1350 cm -1 The D peak is at the center.

[0083] Figure 4 This is a test diagram of the adhesion strength of the amorphous carbon-based coating obtained in Example 2, which shows that the adhesion strength of the coating is 10.2N.

[0084] Figure 5The vacuum friction coefficient test results of the amorphous carbon-based coating obtained in Example 2 are shown in Figure 2. The friction coefficient test was conducted using a self-developed MSTS-1 multifunctional friction and wear tester. The test was conducted under a load of 3N, a friction radius of 6mm, a rotation speed of 500rpm, and a vacuum degree of <3*10 -3 Pa. Figure 5 It can be seen that the friction coefficient of the coating does not exceed 0.03. After the initial friction start-up stage, the friction coefficient is basically stable between 0.01 and 0.02. After 10,000 revolutions, it still maintains a low friction coefficient.

[0085] The amorphous carbon-based coating obtained in Example 2 was irradiated for 50 hours using a self-developed atomic oxygen irradiation (AO irradiation) device, and the typical atomic oxygen flux of the sample was determined to be 2.5×10 15 atoms / cm 2 ·s. Figure 6 This is a surface microscopic morphology of the amorphous carbon-based coating obtained in Example 2 after AO irradiation, which shows that after atomic oxygen irradiation, the tiny particles on the surface of the coating become more uniform, but the cracks become larger. Figure 7 The vacuum friction coefficient test results of the amorphous carbon-based coating obtained in Example 2 after AO irradiation show the vacuum tribological properties of the coating after atomic oxygen irradiation. Affected by atomic oxygen irradiation, the friction coefficient increases, but the friction coefficient is still less than 0.04 in all stages of wear, which is already a very low level.

[0086] Figure 8 The vacuum friction coefficient test results of the amorphous carbon-based coating obtained in Example 3 are shown in Figure 3. The friction coefficient test was conducted using a self-developed MSTS-1 multifunctional friction and wear tester. The test was conducted under a load of 3N, a friction radius of 6mm, a rotation speed of 500rpm, and a vacuum degree of <3*10 -3 Pa. Figure 8 It can be seen that the friction coefficient of the coating does not exceed 0.03, and there are small fluctuations in the entire friction cycle. After 10,000 revolutions, it still maintains a low friction coefficient.

[0087] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. An amorphous carbon-based coating resistant to atomic oxygen corrosion, characterized in that: It includes a transition layer and a functional layer sequentially stacked on the surface of the substrate; The transition layer comprises a chromium layer, a chromium nitride layer and a chromium nitride carbide layer which are stacked; the chromium layer is in contact with the substrate; The functional layer is a lead-doped hydrogenated amorphous carbon layer, and the chromium carbide nitride layer is in contact with the functional layer.

2. The amorphous carbon-based coating according to claim 1, characterized in that The thickness of the chromium layer is 50-100 nm; the thickness of the chromium nitride layer is 100-150 nm; the thickness of the chromium nitride carbide layer is 150-250 nm; The thickness of the transition layer is 0.3-0.5 μm.

3. The amorphous carbon-based coating according to claim 1, characterized in that The atomic percentage of lead in the functional layer is 30-50%, and the atomic percentage of carbon is 50-70%; The thickness of the functional layer is 2.5-3.5 μm.

4. The amorphous carbon-based coating according to claim 1, characterized in that The substrate includes a single crystal silicon wafer or a stainless steel substrate; The surface roughness of the substrate does not exceed 1 / 10 of the thickness of the amorphous carbon-based coating.

5. The amorphous carbon-based coating according to claim 1, characterized in that The surface roughness of the amorphous carbon-based coating is 1-10 nm; the vacuum average friction coefficient of the amorphous carbon-based coating is 0.005-0.

02.

6. The method for preparing an amorphous carbon-based coating resistant to atomic oxygen corrosion according to any one of claims 1 to 5, characterized in that: The following steps are involved: pretreating the substrate to obtain a pretreated substrate; A transition layer and a functional layer are sequentially prepared on the surface of the pretreated substrate to obtain the amorphous carbon-based coating.

7. The preparation method according to claim 6, characterized in that: The pretreatment process is: using argon plasma to bombard the substrate for etching pretreatment; The bombardment etching pretreatment condition parameters include: using inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -500 to -700 V, and a time of 20 to 30 minutes.

8. The preparation method according to claim 6, characterized in that: The transition layer and the functional layer are both prepared by magnetron sputtering deposition; The magnetron sputtering deposition conditions of the chromium layer include: using an inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power source power corresponding to the chromium target of 1.5 to 2 kW, and a sputtering time of 20 to 30 min; The magnetron sputtering deposition conditions of the chromium nitride layer include: using an inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power supply power corresponding to the chromium target of 1.5 to 2 kW, a nitrogen flow rate of 30 to 50 sccm, and a sputtering time of 20 to 30 min; The condition parameters of the magnetron sputtering deposition of the chromium nitride carbide layer include: using an inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power supply power corresponding to a chromium target of 1.5 to 2 kW, a sputtering power supply power corresponding to a graphite target of 4.5 to 6 kW, a nitrogen flow rate of 30 to 50 sccm, and a sputtering time of 20 to 30 min.

9. The preparation method according to claim 8, characterized in that: The condition parameters of the magnetron sputtering deposition of the functional layer include: using an inert gas as a gas source, a flow rate of 100 to 150 sccm, a negative bias voltage of -80 to -100 V, a sputtering power supply power corresponding to a graphite target of 4.5 to 6 kW, a sputtering power supply power corresponding to a lead target of 1 to 2 kW, a hydrocarbon-containing gas flow rate of 80 to 100 sccm, and a sputtering time of 150 to 180 min.

10. Use of the atomic oxygen corrosion-resistant amorphous carbon-based coating according to any one of claims 1 to 5 or the atomic oxygen corrosion-resistant amorphous carbon-based coating prepared by the preparation method according to any one of claims 6 to 9 in devices used in space environments.